3D natural interface to teach piano for beginners - Pang, Hao Jie; Zainal Azmi, Nurazlin (KICT Publishing, 2024)
In this project, we use the Leap Motion controller together with Unity engine to develop a virtual piano application to teach beginners how to play the piano. With Leap Motion, the users can interact with the application as if they are playing it in the real world. The proposed system and its implementation are described. A usability test is also conducted to identify the effectiveness of the application for learning purposes.